PENYUSUNAN STANDAR PELAYANAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN TAKALAR - Sayuti, Nuraeni; Nasir, Abd Wahid (ADMIT: Jurnal Administrasi Terapan, 2023)
Every government is obligated to offer services to its citizens. Indonesia, in particular, has an archipelagic geography, resulting in a widely dispersed society. To address all basic necessities, the Indonesian state established regional autonomy. Every citizen has the right to perform administrative services obtained from the government as a public service provider. Regional Government agency are the agency with the highest amount of complaints in Indonesia, particularly in South Sulawesi, which ranks fourth in terms of service complaints. DPMPTS Takalar Regency, which has occupied the yellow zone in service, continues to encounter numerous barriers in public services, such as the lack of service procedures documented in service standards, thus service standards must be developed. This study employed interviewing, observation, and document examination. The ultimate product of this research is a set of service standards developed in accordance with the criteria for developing service standards from PERMENPAN RB number 15 of 2014. This work provides a solution to problems that may develop.